2017
DOI: 10.1186/s13012-017-0625-5
|View full text |Cite
|
Sign up to set email alerts
|

How do stakeholders from multiple hierarchical levels of a large provincial health system define engagement? A qualitative study

Abstract: BackgroundEngaging stakeholders from varied organizational levels is essential to successful healthcare quality improvement. However, engagement has been hard to achieve and to measure across diverse stakeholders. Further, current implementation science models provide little clarity about what engagement means, despite its importance.The aim of this study was to understand how stakeholders of healthcare improvement initiatives defined engagement.MethodsParticipants (n = 86) in this qualitative thematic study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 63 publications
0
65
0
Order By: Relevance
“…Three contributions of implementation science Stakeholder engagement Stakeholder engagement at the beginning and throughout the research process can enhance the acceptability of interventions to recipients and providers and improve reach (number of eligible people taking part in the intervention) and sustainability (changes over time in numbers of eligible people taking part in the intervention). Recent conceptual development of stakeholder engagement has identified three core elements: active participation from committed stakeholders; stakeholder connectedness around a shared purpose; and meaningful, respectful interaction (Norris et al, 2017). Stakeholder analysis provides a useful heuristic tool which focuses on how to identify and involve key stakeholders in relation to their likely interest, influence and position in the system (Varvasovsky and Brugha, 2000).…”
Section: The Contribution Of Implementation Sciencementioning
confidence: 99%
“…Three contributions of implementation science Stakeholder engagement Stakeholder engagement at the beginning and throughout the research process can enhance the acceptability of interventions to recipients and providers and improve reach (number of eligible people taking part in the intervention) and sustainability (changes over time in numbers of eligible people taking part in the intervention). Recent conceptual development of stakeholder engagement has identified three core elements: active participation from committed stakeholders; stakeholder connectedness around a shared purpose; and meaningful, respectful interaction (Norris et al, 2017). Stakeholder analysis provides a useful heuristic tool which focuses on how to identify and involve key stakeholders in relation to their likely interest, influence and position in the system (Varvasovsky and Brugha, 2000).…”
Section: The Contribution Of Implementation Sciencementioning
confidence: 99%
“…Scholars even argue that the definition of engagement is murky . Norris et al attempt to debunk the murky concept of engagement and identify three modalities including active participation coupled with information sharing and shared decision making; a shared decision making process; and two‐way interactions with mutual respect throughout the process where all stakeholders feel heard and understood . Going by the common elements that define engagement as “an active and committed decision‐making about a meaningful problem through respectful interactions and dialog where everyone's voice is considered”, we conclude that the majority of respondents in our study were not engaged in the development of HSSPs.…”
Section: Discussionmentioning
confidence: 65%
“…This challenge is elucidated by O'Meara et al in their study on community and facility level engagement in planning and budgeting in Kenya where there were differences in priorities identified by community members, facility staff, and the national level MoH. Scholars even argue that the definition of engagement is murky . Norris et al attempt to debunk the murky concept of engagement and identify three modalities including active participation coupled with information sharing and shared decision making; a shared decision making process; and two‐way interactions with mutual respect throughout the process where all stakeholders feel heard and understood .…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to assess the time, effort, and organizational cost of facilitating PCMHI implementation. Additionally, it is the first study of facilitation cost to include stakeholders participating in implementation facilitation activities, which is vital for implementation success [37,38]. Our study found that clinics which needed assistance to implement PCMHI may require substantial organizational investment in resources.…”
Section: Discussionmentioning
confidence: 86%